Risk factors related with avascular necrosis after internal fixation of femoral neck fractures in children: a systematic review and meta-analysis - Qi, Bo-Hai; Wang, Xiao-Wei; Wang, Xiao-Ming; Wang, Huan; Yang, Ya-ting; Jie, Qiang (Frontiers in Pediatrics, 2023)
Background Less than 1% of children develop femoral neck fractures (FNF), making them uncommon. However, they may have dangerous side effects, like avascular necrosis. Even though several risk factors for postoperative avascular necrosis have been identified, there is still debate regarding them. In this investigation, a meta-analysis was performed to examine the potential causes of postoperative avascular necrosis in children with FNF. Methods We conducted a thorough literature search to find risk factors for avascular necrosis (AVN) after internal fixation of pediatric FNF. Until December 2022, we searched several databases, including PubMed, Embase, Cochrane Library, Web of Science, CNKI, Orthosearch, and Sinomed. Software Zotero 6.0 and Stata 17.0 were used to organise and synthesise the data. Finally, a sensitivity and publication bias test was carried out. Results Our study includes a total of 15 case-control studies involving 814 patients. The risk of postoperative AVN increased with age at fracture encounter (95% CI: 0.64–1.88, P = 0.0003), initial fracture displacement (95% CI: 1.87–9.54, P = 0.0005), and poor fracture reduction (95% CI:1.95–22.34, P = 0.0024) were risk factors for postoperative AVN. There was no significant relationship between gender and postoperative AVN (95% CI: 0.52–1.31, P = 0.41). Conversely, Postoperative AVN and reduction methods have no connection with each other (95% CI: 0.77–2.66, P = 0.25), procedure time (95% CI: 0.43–2.99, P = 0.16), or injury mechanism (95% CI: 0.32–2.26, P = 0.75). The incidence of post-operative AVN varies between Delbet fracture types (95% CI: 0.15–0.31, P < 0.0001), with the overall trend being that the incidence of post-operative AVN is highest for type II, lowest for type IV, and close for types I and III, but it is not clear which type of fracture is the independent risk factor. Funnel plots indicate no significant publication bias. Conclusions In line with this study, About 26% of children who underwent surgery for a femoral neck fracture suffered postoperative AVN. The main risk factors for AVN were the child's age, the initial displacement of the fractures, and poorly reduced fractures. The risk of AVN did not significantly correlate with gender, the time of the procedure, reduction methods or the mechanism of injury. The overall trend in the incidence of postoperative AVN for the different Delbet types of fracture is that the incidence of postoperative AVN is highest for type II, lowest for type IV, and close for types I and III, but it is not clear which type of fracture is the independent risk factor.